Do grain boundaries dominate non-radiative recombination in CH3NH3PbI3 perovskite thin films?. Issue 7 (7th February 2017) - Yang, Mengjin; Zeng, Yining; Li, Zhen; Kim, Dong Hoe; Jiang, Chun-Sheng; van de Lagemaat, Jao; Zhu, Kai
Abstract : We examine grain boundaries (GBs) with respect to non-GB regions in high-quality perovskite films using fluorescence-lifetime imaging. We show that recombination happens in the non-GB regions and that GBs are not transparent to photogenerated carriers. Abstract : Here, we examine grain boundaries (GBs) with respect to non-GB regions (grain surfaces (GSs) and grain interiors (GIs)) in high-quality micrometer-sized perovskite CH3 NH3 PbI3 (or MAPbI3 ) thin films using high-resolution confocal fluorescence-lifetime imaging microscopy in conjunction with kinetic modeling of charge-transport and recombination processes. We show that, contrary to previous studies, GBs in our perovskite MAPbI3 thin films do not lead to increased recombination but that recombination in these films happens primarily in the non-GB regions ( i.e., GSs or GIs). We also find that GBs in these films are not transparent to photogenerated carriers, which is likely associated with a potential barrier at GBs. Even though GBs generally display lower luminescence intensities than GSs/GIs, the lifetimes at GBs are no worse than those at GSs/GIs, further suggesting that GBs do not dominate non-radiative recombination in MAPbI3 thin films.